Fire Across the Sea : the Vietnam War and Japan 1965-1975. - Havens, Thomas R. H. (Princeton legacy library., 2014)
Professor Havens analyzes the efforts of Japanese antiwar organizations to portray the war as much more than a fire across the sea"" and to create new forms of activism in a country where individuals have traditionally left public issues to the authorities. This path-breaking study examines not only the methods of the protesters but the tightrope dance performed by Japanese officials forced to balance outspoken antiwar sentiment with treaty obligations to the U.S. Originally published in 1987. The Princeton Legacy Library uses the latest print-on-demand technology to agai